Influence of Magnetic Field on Silver Nanoparticles Synthesized by Laser Ablation - Abbas, Zahraa Marid; Adnan, Qusay (Iraqi Journal of Science, 2020)
Laser ablation of a silver target immersed in distilled water using Nd:YAG laser with a fundamental wavelength of 1064nm was carried out to fabricate silver nanoparticles (Ag NPs) with different laser energy in the presence and absence of magnetic field. UV-Visible spectrum showed that the nanoparticles are almost spherical in shape. The number of Ag NPs increased by increasing laser energy while their particle size was reduced by increasing laser energy without magnetic field. In the presence of magnetic field, the size of Ag NPs increased slightly by increasing laser energy. According to AFM results, the presence of magnetic field did not affect the average diameter of Ag NPs. The presence of a magnetic field causes a change in grain size of Ag NPs with increasing laser energy. While XRD data illustrated that the magnetic field causes an increase in the crystallite size of Ag NPs.